Pelvic organ prolapse and associated factors among women admitted to gynecology ward at the Hiwot Fana Comprehensive Specialized Hospital, Harar, eastern Ethiopia - Abdek Ali; Elias Yadeta; Addis Eyeberu; Lemesa Abdisa; Miressa Bekana; Merga Dheresa (SAGE Open Medicine, 2022)
Objectives: The major aim of this study was to assess the magnitude of pelvic organ prolapse and its associated factors among patients admitted to the gynecology ward at Hiwot Fana Specialized University Hospital, eastern Ethiopia. Methods: A retrospective review of records was undertaken at Hiwot Fana Specialized University Hospital. We used a simple random sampling technique to pick 387 gynecology ward–admitted patient records from 30 December 2020 to 10 January 2021. Data were extracted from maternal medical charts using a pretested checklist. The extracted data were entered into EpiData version 3.1 and then exported into SPSS version 25 for analysis. Binary logistic regression was carried out to observe a significant correlation between independent and pelvic organ prolapse. An adjusted odds ratio and 95% confidence interval was used to report the result. A p-value of less than 0.05 was used to declare statistical significance. Results: Among 387 responded women, 39 (10.1%; 95% confidence interval = 8.3–15.6) of them had at least one stage of pelvic organ prolapse. Multiparty (adjusted odds ratio = 1.88, 95% confidence interval = 1.41–10.60), grand multiparty (adjusted odds ratio = 2.63, 95% confidence interval = 1.53–12.90), older maternal age (adjusted odds ratio = 2.29, 95% confidence interval = 1.220–7.52), lifting a heavy object (adjusted odds ratio = 4.61, 95% confidence interval = 2.31–15.83), and having chronic cough (adjusted odds ratio = 2.39, 95% confidence interval = 1.10–5.19) were significantly associated with pelvic organ prolapse. Conclusion: Among women admitted to the hospital because of gynecological morbidity, one in ten of them had pelvic organ prolapse. Multiparty, advanced maternal age, having a chronic cough, and lifting heavy objects were identified to be risk factors for pelvic organ prolapse. Tailored primary prevention would enhance the well-being of reproductive-age women.